Single Layer versus Double Layer Technique for Intestinal Anastomosis: A Comparative Study - Adhikari, Bimarsh (Journal of Nepalgunj Medical College, 2021)
Introduction: Intestinal anastomosis is a surgical procedure executed to ascertain communication between two segments of the intestine, after the removal of pathology affecting the bowel. It depends on factors like anastomosis site, bowel capability and the type of the pathogenesis.Aims: To compare single versus double layer method in terms of time taken for anastomosis, hospital stay, post-operative leak and cost effectiveness.Methods: This is a comparative hospital based study carried out at the department of surgery Nepalgunj Medical College from September 2017 to August 2020. Patients requiring emergency laparotomy with resection and anastomosis of small bowel were included. Patients requiring colonic anastomosis, diversion stoma and multiple anastomoses were excluded. Patients were divided in to two groups- single layer and double layer group. Each group was compared for outcome measures like time taken to construct the anastomosis, hospital stay, post-operative leak and cost of surgery.Results: The total number of patients was 50. The mean age was 45.57±17.42 years for single layer and 48.67±18.16 years for double layer group. Time taken for intestinal anostomosis in single and double layer were 18.28±5.08 and 25.27±6.18 respectively which was statistically significant (p - 0.342). Similarly, the anastomosis leak was seen in 2 patients in single layer and 3 in double layer. Which was statistically not significant (p - >0.318). While comparing the cost effectiveness single layer technique was cost effective.Conclusion: The single layer anastomosis is a preferable, safe and economic technique in comparison to the conventional double layered anastomosis.